2013
DOI: 10.1038/hdy.2013.82
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of processes shaping the clonal dynamics and genetic mosaic of seagrasses through temporal genetic monitoring

Abstract: Theoretically, the dynamics of clonal and genetic diversities of clonal plant populations are strongly influenced by the competition among clones and rate of seedling recruitment, but little empirical assessment has been made of such dynamics through temporal genetic surveys. We aimed to quantify 3 years of evolution in the clonal and genetic composition of Zostera marina meadows, comparing parameters describing clonal architecture and genetic diversity at nine microsatellite markers. Variations in clonal stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 50 publications
8
40
1
Order By: Relevance
“…Other studies that revealed paradoxical spatial patterns of genetic diversity (e.g., chaotic genetic patchiness; Johnson and Black 1982) may simply be revealing the underlying variance associated with small samples sizes (see Becheler et al 2010Becheler et al , 2013 for alternative explanations). For example, for the smallest sample size in Fig.…”
Section: Sgs An Elusive Yet Biologically Important Patternmentioning
confidence: 96%
“…Other studies that revealed paradoxical spatial patterns of genetic diversity (e.g., chaotic genetic patchiness; Johnson and Black 1982) may simply be revealing the underlying variance associated with small samples sizes (see Becheler et al 2010Becheler et al , 2013 for alternative explanations). For example, for the smallest sample size in Fig.…”
Section: Sgs An Elusive Yet Biologically Important Patternmentioning
confidence: 96%
“…Fine-grained analysis of clonal lineage distribution in Zostera marina Linnaeus, 1753, revealed a large influence of clonality, leading to a mosaic pattern of genetic patchiness. This pattern is largely driven by patchy events of recolonization followed by the occupation of space through clonal spread, despite the likely occurrence of much larger scale effective migration (Becheler et al 2010(Becheler et al , 2014. The genetic concept of populations, based on panmixia, remains elusive in those partially clonal organisms.…”
Section: Taxonomic Knowledgementioning
confidence: 99%
“…We expected that restoration would result in an increase in vegetative multiplication of the species due to higher water levels after the restoration event compared to the pre-restoration stage. As a consequence, we expected a greater decline in clonal richness over time in restored wetlands vs. unrestored wetlands when comparing the two conditions over the same period of time (Becheler et al, 2014). Additionally, as vegetative propagation increases the probability of genotype survival over time, we hypothesised that genetic diversity would remain more stable in restored wetlands than in unrestored reference wetlands over time, even if clonality potentially increased over time in restored wetlands.…”
Section: Introductionmentioning
confidence: 96%
“…During a 3-year-long study, Becheler et al (2014) observed that select genets persisted and extended over time, whereas other genets were recruited each year. However, they only highlighted the stability of genetic diversity over the time scale of the study.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation